2022
DOI: 10.1186/s12944-022-01691-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyslipidemia, treatment rate and its control among patients with type 2 diabetes mellitus in Northwest China: a cross-sectional study

Abstract: Background The prevalence of cardiovascular disease (CVD) is high in China, especially in Northwest China, and dyslipidemia in diabetes is a major factor at risk for CVD. The dyslipidemia prevalence, treatment and control among type 2 diabetes mellitus (T2DM) patients in Northwest China were investigated. Methods In the cross-sectional retrospective research, 1386 medical records of T2DM patients were collected from the Endocrine Department of Tang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Studies on achieving ABC goals in diabetes have focused primarily on LDL-C control [ 54 ]. The overall control rate of LDL-C and non-HDL-C among patients with T2D in China has been reported at 43.1% and 19.8%, respectively [ 55 ]. Among patients with T2D in Iran, the achievement of LDL-C ≤100 mg/dl was 48.1% [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on achieving ABC goals in diabetes have focused primarily on LDL-C control [ 54 ]. The overall control rate of LDL-C and non-HDL-C among patients with T2D in China has been reported at 43.1% and 19.8%, respectively [ 55 ]. Among patients with T2D in Iran, the achievement of LDL-C ≤100 mg/dl was 48.1% [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…T2DM, hypertension, and hyperlipidemia were diagnosed by endocrinologists based on the latest guidelines ( 2 , 12 , 20 ), as described in detail in our previous articles ( 21 , 22 ). The diagnosis of diabetic microvascular complications is firstly caused by diabetes, excluding the other primary causes.…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been many studies correlating diabetic microvascular complications with lipid profiles, the findings have been highly debated. In addition, previous research from our group found that the dyslipidemia rate is very high in patients with diabetic complications [ 9 ]. However, it is unclear which lipid profiles have a greater impact on diabetic complications.…”
Section: Introductionmentioning
confidence: 93%